DEPENDENCE OF THE SEISMIC SUBSIDENCE THRESHOLD ON SOIL STRENGH (Web of Teachers: Inderscience Research, 2025)
The article is devoted to research on the relationship between the ability of soil to settle under seismic action and its strength. It is emphasized that the ability of soil to settle under seismic action depends on the amount of soft bonding strength between particles.